2000
DOI: 10.1177/026988110001400419
|View full text |Cite
|
Sign up to set email alerts
|

Different effect of desipramine on locomotor activity in quinpiroletreated rats after repeated restraint and chronic mild stress

Abstract: We have studied the effect of chronic treatment with the tricyclic antidepressant drug desipramine on locomotor activity in rats challenged with the administration of the D2-like dopamine agonist quinpirole, after prolonged exposure to two different stress regimens, repeated restraint stress and chronic mild stress (different stressors randomly presented). These stress schedules have been previously reported to influence in opposite ways the sensitivity to the locomotor response mediated by the stimulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Dopamine is believed to play a critical role in the neurobiology of depression and in the mechanism of action of antidepressant drugs, a hypothesis based on clinical and preclinical observations (Willner, 1983b;Fibiger, 1995;Charney, 1998;D'Aquila et al, 2000b). As stated above, compounds acting as agonists on dopamine D 2 /D 3 receptors, such as bromocriptine, piribedil, pramipexole, and roxindole (Post et al, 1978;Bouras and Bridges, 1982;Willner, 1983a;Borsini et al, 1988;Muscat et al, 1992;Grunder et al, 1993;Willner et al, 1994;Maj et al, 1996b;Corrigan et al, 2000), and compounds that enhance dopamine levels inhibiting selective dopamine reuptake like amineptine, nomifensine, and bupropion (Kinney, 1985;Dalery et al, 1997), have shown antidepressant-like activity in both preclinical models and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine is believed to play a critical role in the neurobiology of depression and in the mechanism of action of antidepressant drugs, a hypothesis based on clinical and preclinical observations (Willner, 1983b;Fibiger, 1995;Charney, 1998;D'Aquila et al, 2000b). As stated above, compounds acting as agonists on dopamine D 2 /D 3 receptors, such as bromocriptine, piribedil, pramipexole, and roxindole (Post et al, 1978;Bouras and Bridges, 1982;Willner, 1983a;Borsini et al, 1988;Muscat et al, 1992;Grunder et al, 1993;Willner et al, 1994;Maj et al, 1996b;Corrigan et al, 2000), and compounds that enhance dopamine levels inhibiting selective dopamine reuptake like amineptine, nomifensine, and bupropion (Kinney, 1985;Dalery et al, 1997), have shown antidepressant-like activity in both preclinical models and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been proposed that an increase in dopamine activity induced by chronic antidepressant treatments is one of the mechanisms of action underlying the efficacy of these compounds, since their effects are antagonized by low doses of D 2 /D 3 antagonists (Borsini et al, 1984;Borsini et al, 1985a, b;Pulvirenti and Samanin, 1986;Sampson et al, 1991;Serra et al, 1992;D'Aquila et al, 2000a). Moreover, antidepressant treatments are associated with increased dopaminergic function in the mesolimbic system and increased behavioral response to dopamine agonists (Spyraki and Fibiger, 1981;Maj et al, 1984a, b;Cervo and Samanin, 1987;De Montis et al, 1990;Ainsworth et al, 1998a;D'Aquila et al, 2000bD'Aquila et al, , 2003, which takes place after chronic treatment (2-3 weeks), a period of time that correlates with that necessary for the onset of antidepressant activity in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…To take fi rst the behavioural pharmacological observations: CMS-induced anhedonia is associated with decreased place conditioning to DA agonists (amphetamine and quinpirole), and a decrease in the psychostimulant effects of DA agonists (amphetamine and quinpirole) [49,[146][147][148] . By contrast, CMS-induced 'prohedonia' is reported to be associated with increased place conditioning to a DA agonist (cocaine) and increased psychostimulant effects of DA agonists (amphetamine and quinpirole) [142,143,145] .…”
Section: Neurobiological Correlatesmentioning
confidence: 99%
“…Chronic stress and antidepressant treatment, which produce opposite changes in positively motivated behavior, have been shown also to produce a series of opposing changes in receptor and neuronal function in this system. These effects which include alterations in α 1 -adrenergic (Maj and Rogóz, 1999), 5HT1 (Ossowska et al, 2001;Srinivas et al, 2001), 5HT2A (Ossowska et al, 2001;Esposito, 2006), D1 (Ossowska et al, 2001;Huzarska et al, 2006), D2 (D'Aquila et al, 2000), GR and MR (Holsboer, 2001;Schule, 2007) as well as in neurotrophin release (Duman and Monteggia, 2006) and neuronal morphology McEwen, 2003). These multiple correlated effects appear to be the results of a combination of factors including altered neurotransmitter, cytokine, corticosteroid and neurotrophin release (Duman and Monteggia, 2006;Bisagno et al, 2000;McEwen, 2000).…”
Section: ) Positive Motivational Networkmentioning
confidence: 99%